A Multiple Myxoma in Right Ventricle and Right Atrium - Nahar, Samsun; Uddin, Helal; Begum, Fatema; Momenuzzaman, -; Khan, KN (University Heart Journal, 2018)
We are reporting a case of multiple myxoma in right atrium and right ventricle in a 55 years male. Dignosis of myxomas were incidental when he was under evaluation for heart failure.Diagnosis was done by both echocardiography and CT scan of chest. Myxomas originating from the right ventricle and right atrium are even less common and can present unusual diagnostic and therapeutic challenges. University Heart Journal Vol. 13, No. 1, January 2017; 33-35